Evaluation of bispyribac-sodium for weed control in rainfed rice. - Esqueda-Esquivel, Valentín Alberto (2004)
Two experiments were established in LosNaranjos, Veracruz, México to evaluate the weed controlefficacy of the postemergence herbicide bispyribac-sodium,alone and in mixture with other herbicides in rainfed rice andto evaluate the toxicity of bispyribac-sodium to rice. Anexperiment was established on June 13, 1999, and the secondon June 9, 2000 with rice cv Milagro Filipino at 100 kg/ha. Arandomized complete block design with eight treatments andthe second six with four replication each one was established.In 1999, weed control was evaluated at 15, 30 and 105 daysafter application (DAA) and in 2000, at 15, 30 and 45 DAA.In both experiments, toxicity was evaluated at 15 and 30DAA. The main weed species were junglerice [Echinochloacolona (L.) Link.], flatsedge (Cyperus iria L.) and Southerncrabgrass [Digitaria ciliaris (Retz.) Koel]. Bispyribacsodiumaffected only emerged plants; this herbicideefficiently controlled flatsedge at 15 g/ha, junglerice at 22g/ha and Southern crabgrass was only partially controlled.When bispyribac-sodium was mixed with clomazone orthiobencarb, grass control was increased and a residualherbicide effect was obtained. Bispyribac-sodium was highlyselective to rice.